High mechanical property silk produced by transgenic silkworms expressing the Drosophila Dumpy - Dai, Xiangping; Ye, Xiaogang; Shi, Liangen; Yu, Shihua; Wang, Xinqiu; Zhong, Boxiong (Frontiers in Bioengineering and Biotechnology, 2024)
Extensive research has been conducted on utilizing transgenic silkworms and their natural spinning apparatus to produce high-performance spider silk fibers. However, research on using non-spider biological proteins to optimize the molecular structure of silk protein and improve the mechanical performance of silk fibers is still relatively scarce. Dumpy, a massive extracellular matrix polypeptide, is essential for preserving the shape and structural integrity of the insect cuticle due to its remarkable tension and elasticity. Here, we constructed two transgenic donor plasmids containing the fusion genes of FibH-Dumpy and FibL-Dumpy. The results indicated the successful integration of two exogenous gene expression cassettes, driven by endogenous promoters, into the silkworm genome using piggyBac-mediated transgenic technology. Secondary structure analysis revealed a 16.7% and 13.6% increase in the β-sheet content of transgenic silks compared to wild-type (WT) silk fibers. Mechanical testing demonstrated that, compared to the WT, HDUY and LDUY transgenic silk fibers exhibited respective increases of 39.54% and 21.45% in maximum stress, 44.43% and 45.02% in toughness, and 24.91% and 28.51% in elastic recovery rate. These findings suggest that Drosophila Dumpy significantly enhanced the mechanical properties of silk, positioning it as an excellent candidate for the development of extraordinary-performance fibers. This study provides rich inspiration for using other biological proteins to construct high-performance silk fibers and expands the possibilities for designing and applying novel biomaterials.